A atribuição de responsabilidade: da cognição ao sujeito - Crespo, Eduardo (2016)
CRESPO, Eduardo; FREIRE, José Célio. A atribuição de responsabilidade: da cognição ao sujeito. Psicologia & Sociedade, Belo Horizonte, v. 26, n. 2, p. 271-279, 2014.